La motricidad fina y el aprestamiento lectoescritor en niños de 4 años - Vera Ruiz, Mariana Angélica (2024)
The present study highlights the relevance of fine motor skills in early childhood education and examines the interrelation between fine motor skills and the development of pre-literacy and pre-writing skills in 4-year-old children, focusing on the context of the "Mi Osito" Early Childhood Education Center in Daule, Guayas. Employing a mixed-methods approach combining qualitative and quantitative methods, the level of awareness among parents regarding the importance of fine motor skills was analyzed, along with the interest and participation of children in activities requiring fine motor abilities. Findings revealed a diversity in parents' understanding of the relevance of fine motor skills in child development. While some displayed limited knowledge, others exhibited a deeper and more active understanding of the subject. Regarding the children, a diversified interest in activities involving fine motor skills, such as drawing, cutting, or manipulating small objects, was observed. However, individual differences in participation and skill level in these activities were also identified. As a result of the research, various recommendations are proposed to enhance the educational quality and development of fine motor skills in 4-year-old children. The use of playful strategies and adapted didactic materials to stimulate fine motor skills in a fun and effective manner is suggested. Furthermore, the importance of strengthening communication between parents and teachers is emphasized, promoting a shared and collaborative understanding of the significance of these skills in child development.